A comprehensive adoption model of M-government services among citizens in developing countries - Sultana, Mst Rebeka; Ahlan, Abdul Rahman; Habibullah, Md (2015)
M-government (Mobile Government) has become popular among many developing countries including Bangladesh. Since m-government is still in early stage of implementation, few studies have identified the acceptance factors of using services among citizen. However, most of the studies identified the adoption factors based on Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), Theory Reason Action (TRA) and trust-related model. This study aims to propose an adoption model suitable for developing countries using Unified Theory of Acceptance and Use of Technology (UTAUT) and model of trustworthiness. Some important factors such as, perceived good governance and less corruption, perceived public value and culture also are included in this model.